KEPEMIMPINAN TRANSFORMASIONAL PROFETIK DALAM MENGEMBANGKAN PESANTREN DI KABUPATEN JEMBER - Umiarso Umiarso (Akademika : Jurnal Pemikiran Islam, 2018)
Abstract Pesantren (Islamic boarding schools) has been continuously aligning its educational system with the needs of society and the times. The development of pesantren is inseparable from the role of kiai in carrying out the institutional transformation. This study focuses on transformational leadership of the kiai in developing the pesantren institution. The results of this study indicate that the concept of developing pesantren is transcultural with the principle of "accepting a new good culture and preserving the old one that is still relevant", based on the vision and mission, directed at an integrative education system which combines the mind and heart traditions using rational domain and spirituality in order to achieve worldly (profanistic) and ukhrawi (sacralistic) goals; transformational leadership styles of a kiai include idealized influence behavior, inspirational inspiration, intellectual stimulation, individual consideration, and individual spiritual greatness; and the implications of transformational leadership include two dimensions, namely the human resources and institutional resources. Therefore, this leadership can be said to be prophetic transformational leadership with the addition of individual spiritual greatness (Five I'S). Keywords: Kiai, Transformational Leadership, and Pesantren Abstrak: Pesantren secara kontinu menyelaraskan sistem kependidikannya dengan kebutuhan masyarakat serta perkembangan zaman. Pengembangan pesantren tidak terlepas dari peran kiai dalam melakukan transformasi kelembagaan. Penelitian ini memfokuskan pada kepemimpinan transformasional kiai dalam mengembangkan kelembagaan pesantren. Hasil penelitian ini menunjukkan bahwa konsep pengembangan pesantren bersifat transkultural dengan prinsip “menerima budaya baru yang baik dan melestarikan budaya lama yang masih relevan”, berpijak pada visi dan misi, diarahkan pada sistem pendidikan integratif yang memadukan antara tradisi akal dan hati menggunakan domain rasional dan spiritualitas untuk mencapai tujuan yang bersifat duniawi (profanistik) dan ukhrawi (sakralistik); gaya kepemimpinan transformasional kiai meliputi perilaku idealized influence, inspirational inspiration, intellectual stimulation, individual consideration, dan individual spiritual greatness; dan implikasi kepemimpinan transformasional meliputi dua dimensi, yaitu dimensi sumberdaya manusia dan kelembagaan. Karenanya, kepemimpinan ini dapat dikatakan kepemimpinan transformasional profetik dengan penambahan individual spiritual greatness (Five I’S). Kata Kunci: Kiai, Kepemimpinan Transformasional, dan Pesantren